Filsafat Ilmu sebagai Dasar Perkembangan Ilmu Pengetahuan - Kartini Kartini; Nur fauziah utami; Nazla dara dinantika; Nadra rifani; Desy febriani daulay; Annur rosida harahap; Ella ermawati (JURNAL EDUKASI NONFORMAL, 2023)
Philosophy of science is philosophy related to other sciences. Philosophy of science also enters into one part of the form of information. Both science and philosophy use a wise way of thinking and effort to deal with/understand the facts of the world and life. Philosophy of science is often associated with critical matters, open and very dedicated to the truth, unless it is concerned with organized and systematic information. Philosophy of science aims to study something and explain the nature of science which has many limitations to achieve a shared understanding of various natural phenomena to become the subject of science itself and that is usually fragmentary.